Not just a pretty picture: Scientific fact visualisation styles, preferences, confidence and recall. (July 2021) - Walsh, Erin I; Sargent, Ginny M; Grant, Will J
Visuals are often used to enhance learning of scientific information. The recent emergence and popularity of comic-style instruction books for adults, such as the 'manga guide to …', shows the possibility of comic style visualisations for the communication of science with adults. This study investigates whether the addition and style of visual accompaniment of scientific information, as used in comic books, influences immediate and short-term fact recall in an adult audience. Participants ( n  = 310 aged 18–79, 52% identified as female) were presented 20 general science facts in one of five styles: (1) text alone, (2) photo with text caption, (3) cartoon with text caption, (4) photo with explanatory agent and a speech bubble, (5) cartoon with explanatory agent and a speech bubble. Immediate recall, and confidence in that recall, was tested following a brief distractor. Participants indicated their preferred presentation style, and short-term recall was tested by a final quiz of all 20 facts. Overall, the most preferred presentation style was cartoon with explanatory agent and text in a speech bubble (26% preferred). There was no single most effective presentation style; there was no significant difference in immediate recall, short term recall or confidence in answers depending on whether the fact was presented as text, photo or cartoon, or the presence or absence of an explanatory agent. However, immediate recall was significantly better when preference was met ( p  < 0.02). We found that the style of visual accompaniment of scientific information in accordance with the 'manga guide to…' format influenced immediate, but not short-term, fact recall in an adult audience when written English literacy, scientific literacy and non-verbal intelligence were taken into account. Short term recall of scientific facts may best be served by presenting facts in multiple styles, or enquiring about and then meeting participant preference for visual accompaniment.